Synthesis and Spectroscopic Studies of Some transition metal Complexes with Mixed ligand of Metformin and Cysteine - I. Al-Abdali, Basim; A. Shakir, Issam M.; M. Nafea, Huda (Iraqi Journal of Science, 2023)
Mixed ligand complexes of Cu(II), Ni(II) and Co(II) with metformin(MTF) as primary ligand and cysteine(Cys) as secondary ligand have been prepared and characterized by elemental analysis, atomic absorption, molar conductivity, magnetic susceptibility measurements, FTIR,UV-Vis ,1H-NMR and 13C-NMR spectral studies. The elemental analysis, atomic absorption data reveal the formation of [1:1:1] [M:MTF:Cys] complexes.The electronic spectra and magnetic moment measurements reveal the presence of complexes in an octahedral geometry and the molar conductivity studies of the complexes indicate their non-electrolytic nature. The infrared and NMR spectral were showed that the chelation behaviour of the ligands towards selected transition metal ions are through two imino groups of MTF and the sulphur atom and the amino nitrogen of cysteine.